Analisis Butir Soal Mata Pelajaran Fisika Pada Siswa Kelas X MA Al-Muzakarah Toniku Kec. Jailolo Selatan (Penelitian Survey Pada Soal Ujian Akhir Semster Ganjil Tahun Ajaran 2022/2023) - Ali, Nursanti; Muhlis, Fahima (KUANTUM: Jurnal Pembelajaran dan Sains Fisika, 2024)
This research is a quantitative research using a survey method. Data collection techniques with documentation. The subjects in this study are all questions and multiple-choice answer sheets for the odd semester final exam of Class X Physics subject. This study analyzes the level of difficulty, differentiation, and effectiveness of tricksters. Quantitative analysis of multiple-choice questions was carried out using the ANATES version 4.00 program. The results of the study showed that out of a total of 15 multiple-choice questions reviewed from the level of difficulty, there were 1 question or 7% in the difficult or high category, 13 questions or 86% in the medium category, and 1 question or 7% in the low or easy category. Based on the discriminating power, it shows that there are 6 question items (40%) in the very good category, 5 question items (33%) in the good category, 1 question item (7%) in the medium category, 1 question item (7%) in the bad category and 2 question items (13%) in the negative or non-discriminatory category. Based on the effectiveness of the deceiver, it was shown that the deceiver had a total of 60 options out of 15 multiple-choice questions that were tested, 55 options functioned well from 15 questions, and 5 options had poor function from 15 questions. Thus, the results of the study show that the Odd Semester Final Exam questions for Physics subjects are 86% good questions and 14% bad questions.